Analysis of Alar Balance in Secondary Cleft Lip With Z-Plasty Technique of Nasal Cartilage. Issue 2 (March 2015) - Yang, Junyi; Chen, Lingfeng; Wu, Yingzhi; Mu, Xiongzheng
<x xml:space="preserve">Abstract</x> Abstract The cleft nasal deformity is a prevailing problem of complex challenge for plastic surgery, especially in the secondary correction. We mainly chose 40 patients with unilateral secondary cleft lip nasal deformity with alar collapse. Based on biomechanics and anatomy of nasal cartilage, we adapt a Z-plasty with cartilage mucosa using the deformed lateral crus of the upper lateral cartilage to support the collapse of lower lateral cartilage. All of our patients were satisfied with the aesthetic morphology after surgery, so we are confident that this method should be considered as an auxiliary treatment to rhinoplasty.